2014
DOI: 10.1242/jeb.110916
|View full text |Cite
|
Sign up to set email alerts
|

Tail autotomy and subsequent regeneration alter the mechanics of locomotion in lizards

Abstract: Animals can undergo significant weight change for a variety of reasons. Autotomy, the voluntary shedding of an appendage in response to a predator stimulus, provides an effective model for measuring the effects of rapid weight change on locomotor behavior and the responses to more gradual weight gain, particularly in lizards capable of both autotomizing and regenerating their tail. Although the general effects of autotomy on locomotor performance are commonly explored, we investigated changes in locomotor mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 52 publications
5
64
2
Order By: Relevance
“…(2) I recorded all postautotomy trials within 1-2 days of initiating autotomy, whereas McElroy and Bergmann recorded their trials 14 days post-autotomy. Following autotomy, it is known that body condition declines as resources are diverted towards regeneration (Dial and Fitzpatrick, 1981;Maginnis, 2006;Naya et al, 2007;Wrinn and Uetz, 2007;Fleming et al, 2009;Jagnandan et al, 2014) and could decrease maximum sprint speeds Fleming et al, 2009). In this study, the autotomized tail represented 6-10% of the intact body weight, which could have enabled greater running speeds immediately after tail loss because lizards had less weight to carry.…”
Section: Kinematic Changes Associated With Tail Lossmentioning
confidence: 89%
See 2 more Smart Citations
“…(2) I recorded all postautotomy trials within 1-2 days of initiating autotomy, whereas McElroy and Bergmann recorded their trials 14 days post-autotomy. Following autotomy, it is known that body condition declines as resources are diverted towards regeneration (Dial and Fitzpatrick, 1981;Maginnis, 2006;Naya et al, 2007;Wrinn and Uetz, 2007;Fleming et al, 2009;Jagnandan et al, 2014) and could decrease maximum sprint speeds Fleming et al, 2009). In this study, the autotomized tail represented 6-10% of the intact body weight, which could have enabled greater running speeds immediately after tail loss because lizards had less weight to carry.…”
Section: Kinematic Changes Associated With Tail Lossmentioning
confidence: 89%
“…Whereas some lizard species ran significantly faster on flat surfaces after losing their tail than with their original tail (Daniels, 1983;Brown et al, 1995), some exhibited decreased arboreal running performance (Brown et al, 1995). In other taxa, tail autotomy either did not affect overall or maximum running speed (Lu et al, 2010;Jagnandan et al, 2014), or it decreased running performance (Martin and Avery, 1998;Goodman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in overall mass and mass distribution that result from full or partial tail loss are also likely to lead to changes in locomotor mechanics. Very few studies have examined locomotor kinetics following autotomy; however, a recent study of the leopard gecko, Eublepharis macularius, demonstrated that these animals adopted a more sprawled hindlimb posture following tail loss, along with reduced peak hindlimb vertical ground reaction forces (see Glossary), corrected for body size (Jagnandan et al, 2014). Similarly, recent work on green anoles, Anolis carolinensis, also demonstrated a more crouched hindlimb posture during perch running after tail autotomy (Hsieh, 2016).…”
Section: Ground Reaction Forcementioning
confidence: 99%
“…Lizard tails and bodies span a range of sizes and proportions, so autotomy events can have a variety of impacts on body mass. For example, an animal with a long slender tail that autotomizes just the tip is likely to experience a negligible change in body mass as compared with animals with more robust tails, which can account for close to 25% of body mass (Higham and Russell, 2010;Jagnandan et al, 2014). Similarly, subsequent shifts in the position of the CoM can be negligible or up to 15-20% of snout-vent length, depending on the amount of tail lost and the relative length and mass of the tail in relation to the body (Fig.…”
Section: Introductionmentioning
confidence: 99%